Epidemiology, Impact and Control of Rabies in Nepal: A Systematic Review. - Brecht Devleesschauwer; Arjun Aryal; Barun Kumar Sharma; Anita Ale; Anne Declercq; Stephanie Depraz; Tara Nath Gaire; Gyanendra Gongal; Surendra Karki; Basu Dev Pandey; Sher Bahadur Pun; Luc Duchateau; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Rabies is a vaccine-preventable viral zoonosis belonging to the group of neglected tropical diseases. Exposure to a rabid animal may result in a fatal acute encephalitis if effective post-exposure prophylaxis is not provided. Rabies occurs worldwide, but its burden is disproportionately high in developing countries, including Nepal. We aimed to summarize current knowledge on the epidemiology, impact and control of rabies in Nepal. METHODS:We performed a systematic review of international and national scientific literature and searched grey literature through the World Health Organization Digital Library and the library of the National Zoonoses and Food Hygiene Research Centre, Nepal, and through searching Google and Google Scholar. Further data on animal and human rabies were obtained from the relevant Nepalese government agencies. Finally, we surveyed the archives of a Nepalese daily to obtain qualitative information on rabies in Nepal. FINDINGS:So far, only little original research has been conducted on the epidemiology and impact of rabies in Nepal. Per year, rabies is reported to kill about 100 livestock and 10-100 humans, while about 1,000 livestock and 35,000 humans are reported to receive rabies post-exposure prophylaxis. However, these estimates are very likely to be serious underestimations of the true rabies burden. Significant progress has been made in the production of cell culture-based anti-rabies vaccine and rabies immunoglobulin, but availability and supply remain a matter of concern, especially in remote areas. Different state and non-state actors have initiated rabies control activities over the years, but efforts typically remained focalized, of short duration and not harmonized. Communication and coordination between veterinary and human health authorities is limited at present, further complicating rabies control in Nepal. Important research gaps include the reporting biases for both human and animal rabies, the ecology of stray dog populations and the true contribution of the sylvatic cycle. INTERPRETATION:Better data are needed to unravel the true burden of animal and human rabies. More collaboration, both within the country and within the region, is needed to control rabies. To achieve these goals, high level political commitment is essential. We therefore propose to make rabies the model zoonosis for successful control in Nepal.